α-Glucosidase Inhibitory Depsidones from the Lichen Parmotrema tsavoense - Duong, Thuc-Huy; Hang, Tai-Xuan-Hoa; Pogam, Pierre Le; Tran, Thanh-Nha; Mac, Dinh-Hung; Dinh, Minh-Hiep; Sichaem, Jirapast (Planta Medica, 2020)
Chemical investigation of the lichen Parmotrema tsavoense led to the isolation of 5 new depsidones, parmosidones F – J (1 – 5). These compounds were structurally elucidated using spectroscopic methods including HRESIMS and 2D NMR data. Compounds 1, 3, and 4 were evaluated for their inhibition of α-glucosidase. All exhibited potent α-glucosidase inhibitory activity with IC50 values ranging from 10.7 to 17.6 µM, which was much lower than that of the positive control acarbose (IC50 449 µM).
Keywords: Parmeliaceae; Parmotrema tsavoense; lichen; parmosidones F – J; depsidone; α-glucosidase inhibition